Penerapan Analytical Hierarchy Process – TOPSIS Dalam Penentuan Marketplace Terbaik di Propinsi Jambi - Rico Rico; Hetty Rohayani; Irmanelly; Endah Tri Kurniasih (JOURNAL VISION TECHNOLOGY (V-TECH), 2023)
The marketplace industry in Indonesia, especially Jambi Province, is starting to grow rapidly over time. Behind its convenience, some users still feel dissatisfied when making transactions. Problems that are often encountered are product incompatibility, delivery problems, types of payment methods, unsatisfactory service, to difficult return policies. In addition, the many considerations such as prices, discounts and promos make users confused about choosing the right marketplace in making transactions. This study applies the AHP-TOPSIS method as a decision support to determine the best marketplace in Jambi Province with the criteria used, namely discounts & promos, services, features, product quality, payment methods, and availability of goods. While the alternatives used are Belanjo, Payo ke Pasar, Angso Duo Online, Kribo, and Wikiniaga. The results of this research are expected to be useful for the community, especially in Jambi Province, in making decisions about choosing the marketplace that best suits their needs and circumstances for conducting transactions.